First detection and genetic characterization of ungulate tetraparvovirus 2 and ungulate tetraparvovirus 4 in special livestock on the Qinghai-Tibet Plateau in China - Pan, Yangyang; Wang, Yun; Wang, Meng; Zhang, Qian; Baloch, Abdul Rasheed; Zhou, Jun; Ma, Jing; Kashif, Jam; Xu, Gengquan; Wang, Libin; Fan, Jiangfeng; Cui, Yan; et al. (Virology journal, 2019)
Tetraparvovirus, formerly known as Partetravirus, is a newly discovered genus in the family Parvoviridae that is considered phylogenetically distinct from other parvoviruses. However, nothing is known about the prevalence of Tetraparvovirus in special livestock living on the Qinghai-Tibet Plateau of China, such as Tibetan pigs and Tibetan sheep. A pair of special primers was designed based on the conserved regions in the genome of ungulate tetraparvovirus 2 (P-PARV4) and ungulate tetraparvovirus 4 (O-PARV4) and was used to detect P-PARV4 in domestic pigs and Tibetan pigs and O-PARV4 in ovines and Tibetan sheep. The results showed a 15.59 and 9.38% prevalence of P-PARV4 in domestic pigs (18.96% in Gansu Province and 11.76% in Qinghai Province) and Tibetan pigs (14.28% in Gansu Province and 4.44% in Qinghai Province), respectively, and a 7.31 and 5.20% prevalence of O-PARV4 in ovines (6.61% in Gansu Province and 8.00% in Qinghai Province) and Tibetan sheep (4.55% in Gansu Province and 5.50% in Qinghai Province), respectively. The prevalence of P-PARV4 was 14.76% (31/210) for ≤1-month-old pigs and 10.58% (20/189) for > 1-month-old pigs, and the positive rates of O-PARV4 were 7.65% (18/235) for ≤1-month-old sheep and 5.05% (11/218) for > 1-month-old sheep. The phylogenetic analysis of NS1, VP1, VP2 and the whole PARV4-related provirus genome demonstrated that both P-PARV4 and O-PARV4 sequences in this study were more closely related to the sequences of other strains discovered in the same genus of animals. The identity analyses for the full-length VP2 genomes of O-PARV4 revealed 98.84-100.00% sequence identity among the 7 strains and the previously reported strain, which was 98.60-99.28% for P-PARV4. In the present study, for the first time, we have provided comprehensive information regarding the widespread infection of P-PARV4 and O-PARV4 in special livestock on the Qinghai-Tibet Plateau in China. Our present findings highlight the importance of epidemiologic surveillance to limit the spread of Tetraparvovirus in livestock at high altitudes in China.
Keywords: Animals; Livestock; Genome, Viral; Qinghai-Tibet plateau; Prevalence; Ungulate tetraparvovirus 4; polymerázová řetězová reakce; dobytek; Polymerase Chain Reaction; China; Viral Proteins; ovce; genom virový; Tibetan sheep; infekce viry z čeledi Parvoviridae; Parvoviridae Infections; prasata; Phylogeny; prevalence; Swine; Sheep; Čína; virové proteiny; Parvovirinae; Sequence Analysis, DNA; Tibetan pig; Ungulate tetraparvovirus 2; zvířata; sekvenční analýza DNA; fylogeneze; Tibet